An in vitro study on the key features of Poly L-lactic acid/biphasic calcium phosphate scaffolds fabricated via DLP 3D printing for bone grafting. (5th December 2020) - Bagheri Saed, Arvin; Behravesh, Amir Hossein; Hasannia, Sadegh; Akhoundi, Behnam; Hedayati, Seyyed Kaveh; Gashtasbi, Fatemeh
Graphical abstract: Highlights: PLLA/BCP bio-composite scaffolds have been assessed for the first time. A 45 wt.% BCP content was the maximum amount for suitable DLP 3D printing. BCP particles improved cell attachment and increased the biodegradation time. BCP particles mitigated the pH reduction effect during the in vitro degradation. Abstract: The main aim of this study was to assess the influence of adding BCP particles on enhancing essential properties of PLLA matrix scaffolds for bone grafting purpose. Poly L-lactic acid (PLLA)/biphasic calcium phosphate (BCP) scaffolds were fabricated via a digital light processing (DLP) 3D printer, with 70% porosity and 600 µm pore size. DLP method was utilized to generate scaffolds with sophisticated geometry, and the bio-composite material was introduced to benefit from positive aspects of polymeric/inorganic substances for bone regeneration. The selected BCP contents were 22.5, and 45 wt% compared with the control specimens with no content. Morphology, exact amount of BCP concentration as well as their distribution were assessed using computerized tomography (µ-CT), thermogravimetry analysis (TGA) and scanning electron microscopy (SEM). Moreover, in vitro biodegradability, cell viability and attachment of the specimens were also investigated. The results showed that in spite of decreasing effect of BCP particles on the mechanical properties of the printed scaffolds, cell adherence and hydrophilicity of the samples were considerably improved. Moreover, a 22.5 wt% of BCP content was found to be an optimum amount to preserve the mechanical properties during biodegradation. The paper showed the effectiveness of adding BCP particles as a biocompatible ceramic to enhance properties of the scaffolds for dental bone regeneration.